Examining first year engineering students' perceptions towards online speaking assessment amidst COVID-19 pandemic - Suradi, Noorsaiyidah; Khoo, Linda Mei Sui; Robani, Anidah; Cheong, Kar Mee (ResearchTrentz Academy Publishing Education Services, 2022)
This study explores First Year Engineering students' perceptions towards online speaking assessment amidst COVID-19 pandemic. To ensure that the education process remained uninterrupted during the pandemic, schools and higher learning institutions were forced to shift to full time remote teaching and learning which has indirectly impacted assessment and evaluation of all courses. This study aims to examine first year engineering students' views on their experience having online speaking assessment amidst covid-19 pandemic. Investigating students' perceptions as the end user towards online assessment is highly crucial to determine the effectiveness of teaching and learning. A quantitative method of study was conducted with questionnaire derived from Technology Acceptance Model (TAM) was adopted to collect responses from 163 undergraduate Diploma engineering students doing their first semester in Universiti Teknikal Malaysia Melaka, Malaysia. The key findings indicated that the students were well receptive of online speaking assessment and were fully ready to have online speaking assessment in the future. The study also discovered that students' perceived self-efficacy towards online speaking assessment was low and there was significant difference in perceptions between students from rural and students from urban area on online speaking assessment. This study is important to higher learning institutions to serve as a guide in making planning related to implementation of online speaking assessment during the pandemic. This research is also significant for its contribution towards language teaching practices in higher learning institution and will be helpful for the educators to identify ways to enhance students' online assessment experience for an effective teaching and learning.